THE INFLUENCE OF FOREIGN OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON THE COMPANY'S FINANCIAL PERFORMANCE (CASE STUDY OF BANKING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE) - Sipayung, Tri Dharma; Simanjuntak, Arthur; Thomas Sumarsan Goh; Simanjuntak, Gracesiela Y; Lase, Arthika Iradat R (Program Studi Akuntansi Universitas Simalungun, 2024)
This study aims to examine the impact of foreign ownership and institutional ownership on the company's financial performance. In this study, financial performance is measured by Return On Assets (ROA). The population in this study includes banking companies listed on the Indonesia Stock Exchange (IDX) and have published financial reports for 2020-2022. The sampling method used purposive sampling technique and as many as 33 companies were sampled in this study. The results showed that foreign ownership has a significant negative effect on the company's financial performance. Furthermore, institutional ownership has no effect on the company's financial performance. The next research results state that foreign ownership and institutional ownership together have a significant positive effect on the company's financial performance